2017
DOI: 10.3233/wor-172612
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work-related musculoskeletal injuries among South Indian hand screen-printing workers

Abstract: Study results infer that HSP workers are prone to lower back and shoulder pain followed by knees and ankle feet regions. Socio-demographic factors, awkward posture and repetitive movements contribute to cause MSD among hand screen-printing workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…stressors is greater in bigger organizations, excepting for role clarity. They are consistent with past research on stress factors (e.g., Dekker and Barling, 1995) and rewards (e.g., Ingham, 1970) and findings that stress is positively related to organizational size (Health and Safety Executive [HSE], 2016) and job satisfaction is negatively related to organizational size (Clark et al, 1996;Bender et al, 2005).…”
Section: Criterion Validitysupporting
confidence: 90%
“…stressors is greater in bigger organizations, excepting for role clarity. They are consistent with past research on stress factors (e.g., Dekker and Barling, 1995) and rewards (e.g., Ingham, 1970) and findings that stress is positively related to organizational size (Health and Safety Executive [HSE], 2016) and job satisfaction is negatively related to organizational size (Clark et al, 1996;Bender et al, 2005).…”
Section: Criterion Validitysupporting
confidence: 90%
“…Work-related MSDs (WMSDS) can cause productivity reduction, decrease work quality,[ 10 ] and increase in absenteeism. [ 11 ] Evidence has shown that reducing and preventing musculoskeletal problems is an important global priority.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Flexor tendon injuries are one of the most common industrial hand injuries occurring due to an increased industrialization around the globe. 4 Usually, among hand injuries the flexor tendon is the most common clinical presentation with or without other associated injuries to the bone and neurovascular structures caused by road traffic accident, industrial accident; glass cut or knife cut and occasionally results in avulsion injuries as well. 5 The prevalence of flexor tendon injuries in an Indian population context is still lacking and is under research.…”
Section: Introductionmentioning
confidence: 99%
“…5 The prevalence of flexor tendon injuries in an Indian population context is still lacking and is under research. 4 A study from the USA estimates an incidence at about 14/100,000-person per years, 6 while a study among the Finnish population puts the figure at 7/100,000-person years. 7 The majority of the hands are either crushed, clamped, rolled-in, or cut or sawed by tools, resulting in impairment and disability.…”
Section: Introductionmentioning
confidence: 99%